Minimal 3-3-1 model, lepton mixing and muonium-antimuonium conversion - Gusso, A.; da Silva, PSR; Pires, CAD (Iop Publishing Ltd, 2004)
The recent experimental results on neutrino oscillation and on muonium-antimuonium conversion require extension of the minimal 3-3-1 model. We review the constraints imposed on the model by these measurements and suggest a pattern of leptonic mixing, with charged leptons in a non-diagonal basis, which accounts for the neutrino physics and circumvents the tight muonium-antimuonium bounds on the model. We also illustrate a scenario where this pattern could be realized.